(untitled) (Conference Zone, 2022)
Alisher Navoi is the cornerstone of Uzbek literature, the great foundation of modern civilizationis a person. The spiritual legacy of this historical figure is centuries old. Only Uzbekwriters, poets, kings and presidents, scholars all over the worldadmired his literary skill and heritage. In this article, the author forms the basis of Navoi’s legacydescribes his analysis of the gazelles.